Pastoral Theology Relevant for Contemporary Indonesia - Jernih Ndruru, Minta; Susanto, Deniel (International Journal Labs, 2025)
Pastoral theology plays a crucial role in responding to social and spiritual challenges in Indonesia, particularly in the context of the increasing divorce rate. This article examines the relevance of pastoral theology in addressing family and marriage issues in Indonesia. Although divorce is undesirable, it is a reality that must be pastorally addressed through a holistic and love-based approach. This study explores the various causes of divorce, the pastoral theological perspective on marriage, and relevant pastoral care methods to support families in crisis. The church is expected to actively provide spiritual guidance, counseling, and social support for congregants facing marital challenges. By integrating biblical teachings with a contextual pastoral approach, church ministry can be more effective in strengthening family resilience and fostering a more harmonious community.